أهمية إدراج معرف الكائن الرقمي DOI على المقالات وأصالة مجلات المنصة الجزائرية للمجلات العلمية - بحشاشي رابح (University Of Eloued جامعة الوادي, 2023)
The study aimed to identify the importance of including the DOI DIGITAL OBJECT IDENTIFIER on the articles and studies that are published on the scientific journals of the Algerian platform and its impact on the originality and credibility of these journals among the rest of the scientific journals at the global level, and the extent of its importance for the researcher and the scientific journal, especially the Algerian platform for journals Scientifically, as it is known that a digital object is a unique digital identifier applied to a specific part of intellectual property. It is an electronic reference technology that has been applied since the year 2000, and it is always in contact with documents or articles as long as they remain on the Internet. The study concluded that the adoption of the digital DOI is urgent and very necessary in order to protect studies from scientific theft, which has spread widely, especially after the opening of the Algerian platform for scientific journals on the Internet without providing the slightest protection for what is published on this platform. The study recommends the importance of speeding up the application This digital identifier as soon as possible due to its importance on the authenticity and credibility of the shops and the Algerian platform for refereed scientific journals.
The importance of including the DOI on articles and the originality of the journals and the Algerian platform for scientific journals
مداخلة
Keywords: DOI; معرف الكائن الرقمي; منصة المجلات; السرقة العلمية; الأنترنت; Digital Object Identifier; Journal Platform; Originality; Plagiarism; Internet